Advances in Nephropathy - Rath, Thomas (IntechOpen, 2018)
Chronic kidney disease (CKD) is a world-wide known disease affecting up to 4% of the population with increasing figures in developing countries. Life expectancy of patients affected by CKD is shortened compared to the overall population and only a minority of patients reach end stage renal disease (ESRD) with the need for dialysis or renal transplantation; death overtakes dialysis. In nine chapters, this book focuses on different aspects related to the pathophysiology and clinical aspects of CKD, providing interesting insights into new and old biomarkers, allowing us to increase diagnostic and prognostic meaningfulness. In addition, chapters deal with new developments in glomerulopathies, but also aspects of the "tubulocentric" shift will be beneficial for the open-minded reader. Nevertheless, new insights into chronic kidney disease (CKD) and acute kidney injury (AKI) are provided.